Beyond Tropical Storms: Understanding Disturbance and Forest Dynamics - Heartsill-Scalley, Tamara; López-Marrero, Tania (Frontiers in Forests and Global Change, 2021)
Most of the knowledge of tropical storm effects on forests is from studies conducted in reserves and protected areas. Effects on other settings such as urban forests, coastal forests, and in landscapes with mixed land uses and covers are, comparatively, less studied. Yet research from such forest types and landscape settings is needed to inform actions associated with management, mitigation, or restoration efforts before and after storms. Studies among various landscape settings, along with long-term observations, would offer unique insights into the varied and cumulative effects of tropical storms on forest ecosystems. We argue that these studies are urgently needed as various forest types within different landscape settings are a significant portion of the landscape affected by storms and other disturbances. Using Puerto Rico as a case study, we demonstrate that most tropical storm-forest studies are generated from a limited set of sites under conditions not representative of the most common forest types and landscape settings. We emphasize the need for broader research approaches in the range of forests that are exposed to tropical storms to advance understanding. Such an approach will provide valuable knowledge and understanding needed to inform and take actions across landscape settings, forest context, and socio-environmental conditions.